Beyond Culture Shock: Intercultural Learning and English Language Adaptation among Sudanese Students in Palembang, Indonesia - Gumartifa, Asti; Marliasari , Sherly; Islami, Maharani Putri (IJORER : International Journal of Recent Educational Research, 2026)
Objective of this study is to explore the culture shock experienced by Sudanese students studying at a university in Palembang, Indonesia, focusing on both students' psychological and sociocultural adaptation challenges and strategies when adapted to a new cultural environment. The method is qualitative descriptive approach, data were collected through questionnaires and unstructured interviews to obtain a deeper exploration of students’ perspectives. As a result, the findings reveal that Sudanese students experienced the four stages of culture shock such as honeymoon, crisis, recovery, and adjustment. During the crisis stage, students reported difficulties related to language barriers, food, climate differences, and communication patterns with local students. Over time, in the recovery and adjustment stages, students gradually adapted by building social networks, improving language skills, and engaging in local cultural practices. Furthermore, this study offers novelty by integrating intercultural adaptation theories and exploring the under-researched experiences of African students in Indonesia by providing insights into how they enhance academic adaptability and sociocultural competence during classroom activities. The findings reveal that social adaptation strategies significantly improved students' English ability by encouraging actual language exposure, improving academic confidence, and promoting greater understanding and production of academic texts.